Molded body for battery protection and method for protecting battery

A thermoplastic resin composition with specific expanding agents addresses the inadequacies of current safety measures by expanding to prevent heat propagation and enhance battery safety during thermal runaway.

JP2025004816APending Publication Date: 2025-01-16TORAY INDUSTRIES INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023104657
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-01-16

AI Technical Summary

Technical Problem

Current safety measures for batteries, such as current breakers and packaging materials, are inadequate in preventing thermal runaway due to low breaking temperatures, insufficient heat propagation prevention, and low productivity, especially in high-output batteries.

Method used

A molded article made of a thermoplastic resin composition containing specific expanding agents, which expands at high temperatures to suppress thermal runaway by increasing thickness and preventing heat propagation.

Benefits of technology

The molded article provides excellent compression creep properties and effective heat propagation prevention, enhancing battery safety by expanding to create space and suppress heat transfer during thermal runaway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004816000001
    Figure 2025004816000001
  • Figure 2025004816000002
    Figure 2025004816000002
Patent Text Reader

Abstract

To provide a molded body for battery protection which has excellent compressive creep properties and can suppress propagation of heat by expanding in a thickness direction at high temperatures, in order to suppress thermal runaway of a battery and achieve safety.SOLUTION: The molded body for battery protection comprises a thermoplastic resin composition. The thermoplastic resin composition is obtained by blending 0.01 pt.wt. or more and 30 pts.wt. or less of an expanding agent (B) based on 100 pts.wt. of a thermoplastic resin (A) with the higher of the glass transition point and the melting point thereof being 150°C or higher and 300°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a molded article for protecting a battery. [Background technology]

[0002] Various types of batteries, such as lithium-ion batteries, can experience thermal runaway due to internal short circuits, resulting in problems such as fire and smoke. In recent years, there has been a trend for automotive batteries and home storage batteries to be densely packed with multiple batteries to achieve higher capacity and output in order to meet the increasing demands on the performance of these batteries. This has increased the load on the batteries, raising the risk of thermal runaway and making safety measures more important.

[0003] Specific examples of safety measures against thermal runaway in batteries include a current breaker (Patent Document 1) in which an insulating layer has a foam layer that foams at a predetermined temperature, and when the battery generates abnormal heat, the thickness increases, causing the contacting connecting plate to separate and cutting off the current flowing between the battery and an external device; a packaging material for batteries that contains a resin and a specific heat-absorbing agent, and the amount of heat absorbed by the entire heat-absorbing agent resin composition is set to a predetermined value or more, thereby suppressing thermal runaway by absorbing heat and preventing the surface temperature of the container from increasing even if thermal runaway occurs (Patent Document 2); and a battery module (Patent Document 3) that is composed of a resin material containing a filler in the resin base material in order to suppress deterioration of adjacent batteries due to heat generated by a battery that has experienced an abnormality, and is equipped with a battery holder made of a resin material with a lower limit for the filler content defined based on the amount of heat absorbed. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-197260 A [Patent Document 2] JP 2020-158159 A [Patent Document 3] International Publication No. 2017 / 125985 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the current breaker proposed in the invention disclosed in Patent Document 1 has a low breaking temperature of about 100°C and low compression creep properties, making it insufficient in reliability as a safety measure for high-output batteries.

[0006] Furthermore, the packaging material proposed in the invention disclosed in Patent Document 2 is a component for transporting batteries, and as a protective component to be directly incorporated into a product, it has the problem that it has low compression creep properties and insufficient heat transmission prevention properties.

[0007] Furthermore, the battery holder proposed in the invention disclosed in Patent Document 3 had the problem that the thermal conductivity of the resin material increased due to the filler added, resulting in insufficient heat transfer prevention properties, and that the thermosetting resin used as the base material required a hardening process during molding, resulting in low productivity.

[0008] An object of the present invention is to provide a molded body for protecting a battery which has excellent compression creep properties in order to suppress thermal runaway of the battery, and which further exhibits excellent heat propagation prevention properties by expanding at high temperatures. [Means for solving the problem]

[0009] As a result of repeated investigations to solve the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using a molded body made of a specific thermoplastic resin mixed with a specific expansion agent as a battery protection part and increasing the thickness of the molded body in a specific temperature environment, thereby arriving at the present invention. That is, the present invention has the following configuration. [1] A molded body for protecting a battery, comprising a thermoplastic resin composition, the thermoplastic resin composition being a blend of 100 parts by weight of a thermoplastic resin (A) having a glass transition point or a melting point, whichever is higher, of 150°C or more and 300°C or less and 0.01 parts by weight or more and 30 parts by weight or less of an expansion agent (B). [2] The molded body for protecting a battery according to [1], which has a thickness expansion coefficient of 1.3 or more when heat-treated for 5 minutes in a high-temperature environment of 380°C. [3] The molded body for protecting a battery according to [1] or [2], wherein the thermoplastic resin (A) is a polybutylene terephthalate resin, and the expansion agent (B) is a melt tension-imparting agent (B1) consisting of a polymer containing a structural unit derived from at least one monomer selected from ethylene, fluoroethylene, styrene, and acrylic. [4] The molded body for protecting a battery according to any one of [1] to [3], wherein the thermoplastic resin (A) is a polybutylene terephthalate resin, and the expanding agent (B) is a nitrogen-based blowing agent (B2) which is at least one selected from the group consisting of an aliphatic amine compound, an aromatic amine compound, a nitrogen-containing heterocyclic compound, a cyan compound, an aliphatic amide compound, an aromatic amide compound, urea, and thiourea. [5] The molded article for protecting a battery according to any one of [1] to [3], wherein the expansion agent (B) is polytetrafluoroethylene or a copolymer thereof. [6] The molded article for protecting a battery according to any one of [1] to [3], wherein the expansion agent (B) is polymethyl methacrylate or a copolymer thereof. [7] The molded body for protecting a battery according to any one of [1], [2], and [4], wherein the expansion agent (B) is melamine cyanurate. [8] The molded body for protecting a battery according to any one of [1] to [7], wherein the thermoplastic resin composition further contains 0.01 to 1 part by weight of a heat stabilizer (C) per 100 parts by weight of the thermoplastic resin (A). [9] A method for protecting a battery, comprising: disposing the battery protective molded article according to any one of [1] to [8] around a battery; and expanding the thickness of the molded article by 1.3 to 10 times in a high-temperature environment of 200°C or higher and 400°C or lower, thereby suppressing heat propagation. Effect of the Invention

[0010] According to the present invention, it is possible to provide a molded body for protecting a battery, which has excellent compression creep properties and is capable of suppressing heat propagation by expanding in the thickness direction at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The battery protection molded article of the present invention will be described in detail below. The battery protection molded article described below relates to a technology for preventing heat transfer to adjacent batteries during thermal runaway of a battery, thereby improving safety, by arranging the molded article around each battery when multiple batteries are stacked and used.

[0012] The mechanism of thermal runaway in batteries is that as the temperature inside the battery rises, a reaction occurs between the electrolyte and the electrodes and the separator melts down, and if the load continues and the temperature rises above 200°C, thermal decomposition of the positive electrode occurs, causing the temperature to rise rapidly to a range of 200-400°C, and eventually reaching the melting point of the aluminum components of the battery container (around 600°C), causing the battery to ignite.It is thought that the heat then spreads to adjacent batteries, causing the thermal runaway to propagate in a chain reaction.

[0013] Therefore, it was found that by placing a battery protection molded body made of a specific thermoplastic resin composition that expands in a specific temperature range of 200 to 400°C while maintaining the battery stably up to around 200°C, around the battery, it is possible to ensure space between the batteries in the event of thermal runaway, thereby suppressing the transmission of heat and making the battery safer.

[0014] The thermoplastic resin composition constituting the molded article for protecting a battery of the present invention will now be described in detail.

[0015] The thermoplastic resin composition of the present invention is a thermoplastic resin composition obtained by blending 100 parts by weight of a thermoplastic resin (A) having a glass transition point or a melting point, whichever is higher, of 150°C to 300°C with 0.01 parts by weight to 30 parts by weight of an expanding agent (B).

[0016] The thermoplastic resin (A) used in the present invention, which has a glass transition point or a melting point, whichever is higher, of 150°C or more (hereinafter, sometimes referred to as "thermoplastic resin (A)" or "(A) component"), may be either an amorphous thermoplastic resin or a crystalline thermoplastic resin that can be plasticized and melted at the glass transition point or melting point or higher. If the glass transition point or melting point of the (A) component is 150°C or higher, the compression creep property of the molded body is excellent, and the battery can be protected even in a high-temperature environment. It is preferably 180°C or higher, and more preferably 200°C or higher. The glass transition point or melting point of the thermoplastic resin (A) is 300°C or lower, more preferably 250°C or lower, from the viewpoint of molding stability. The glass transition point or melting point is a value measured using a differential scanning calorimeter (DSC) under the condition of a temperature increase / decrease rate of 20°C / min, the glass transition point is the midpoint of the baseline shift, and the melting point is the top of the endothermic peak.

[0017] Specific examples of the amorphous thermoplastic resin include polycarbonate resin, polyphenylene oxide resin, polyarylate resin, polyetherimide resin, and polysulfone resin.

[0018] Specific examples of the crystalline thermoplastic resin include polypropylene resin, polyoxymethylene resin, polyketone resin, polybutylene terephthalate resin, polyethylene terephthalate resin, polyamide resin, syndiotactic polystyrene resin, and polyphenylene sulfide resin.

[0019] The component (A) used in the present invention is preferably a crystalline thermoplastic resin because of its excellent durability, and among these, polybutylene terephthalate resin is preferred because of its excellent molding stability and expandability.

[0020] The blowing agent (B) used in the present invention (hereinafter sometimes referred to as "component (B)") includes a melt tension imparting agent (B1) or a nitrogen-based blowing agent (B2), and two of these may be blended together. By blending component (B) with component (A), the thickness of the molded article can be increased by foaming in a high-temperature environment of 200°C to 400°C.

[0021] The melt tension imparting agent (B1) (hereinafter sometimes referred to as "component (B1)") is a polymer containing a structural unit derived from at least one monomer selected from ethylene, fluoroethylene, styrene, and acrylic. It may be a polymer obtained by homopolymerizing at least one monomer selected from ethylene, fluoroethylene, styrene, and acrylic, or a copolymer obtained by copolymerizing a plurality of monomers simultaneously or in multiple stages, and two or more of these may be blended. Blending component (B1) with component (A) can increase the melt tension, and the molded article can be expanded in the thickness direction under high temperature conditions due to the melt tension. From the viewpoint of increasing the melt tension, it is preferable that the polymer has a higher viscosity than component (A).

[0022] Specific examples of the (B1) component include polyethylene, polymethyl acrylate, polybutyl acrylate, polymethyl methacrylate, polystyrene, polytetrafluoroethylene, polyethylene / butene copolymer, polyethylene / octene copolymer, polymethyl methacrylate / butyl acrylate copolymer, polymethyl methacrylate / styrene copolymer, polystyrene / fluoroethylene copolymer, polystyrene / acrylonitrile / fluoroethylene copolymer, polymethyl methacrylate / fluoroethylene copolymer, polybutyl methacrylate / fluoroethylene copolymer, and the like. Among these, polymethyl methacrylate and its copolymers, and polytetrafluoroethylene and its copolymers, which can generate particularly strong melt tension in a high temperature environment, are preferred. Commercially available products of polymethyl methacrylate and its copolymers include "KANEACE (registered trademark) PA-40" manufactured by Kaneka Corporation. Commercially available products of polytetrafluoroethylene and its copolymers include "Teflon (registered trademark) 6J" manufactured by DuPont-Mitsui Fluorochemicals Co., Ltd. and "Metablen (registered trademark) A3800" manufactured by Mitsubishi Chemical Corporation.

[0023] The nitrogen-based blowing agent (B2) (hereinafter sometimes referred to as "component (B2)") is at least one selected from aliphatic amine compounds, aromatic amine compounds, nitrogen-containing heterocyclic compounds, cyanide compounds, aliphatic amide compounds, aromatic amide compounds, urea, and thiourea, and two or more of these may be blended. By blending component (B2) with component (A), it decomposes in a high-temperature environment to generate a gas containing nitrogen and the like, and the molded body can be expanded in the thickness direction.

[0024] Examples of the aliphatic amine compound include ethylamine, butylamine, diethylamine, ethylenediamine, butylenediamine, triethylenetetramine, 1,2-diaminocyclohexane, and 1,2-diaminocyclooctane.

[0025] Examples of the aromatic amine compound include aniline and phenylenediamine.

[0026] Examples of the nitrogen-containing heterocyclic compound include uric acid, adenine, guanine, 2,6-diaminopurine, 2,4,6-triaminopyridine, and triazine compounds.

[0027] The cyanide compound may be dicyandiamide.

[0028] Examples of the aliphatic amide compound and aromatic amide compound include N,N-dimethylacetamide and N,N-diphenylacetamide.

[0029] The triazine compound exemplified in the nitrogen-containing heterocyclic compound is a compound having a triazine skeleton. For example, triazine, melamine, benzoguanamine, methylguanamine, cyanuric acid, melamine cyanurate, melamine isocyanurate, trimethyltriazine, triphenyltriazine, amelin, amelide, thiocyanuric acid, diaminomercaptotriazine, diaminomethyltriazine, diaminophenyltriazine, diaminoisopropoxytriazine, and melamine polyphosphate can be mentioned, and melamine cyanurate, melamine isocyanurate, and melamine polyphosphate are preferably used.

[0030] The melamine cyanurate or melamine isocyanurate is preferably an adduct of cyanuric acid or isocyanuric acid and a triazine compound, and may be an adduct having a composition of 1:1 (molar ratio) or 1:2 (molar ratio) in some cases. These are produced by known methods, and are generally obtained in powder form by, for example, making a mixture of melamine and cyanuric acid or isocyanuric acid into a water slurry, thoroughly mixing the mixture to form the salts of both in the form of fine particles, filtering the slurry, and drying the slurry. The above salts do not need to be completely pure, and some unreacted melamine, cyanuric acid, or isocyanuric acid may remain. In addition, when the dispersibility is poor, a dispersant such as tris(β-hydroxyethyl)isocyanurate or a known surface treatment agent such as polyvinyl alcohol and a metal oxide such as silica may be used in combination. In addition, the average particle size of melamine cyanurate or melamine isocyanurate before and after being mixed with a resin is preferably 0.1 to 100 μm in terms of the flame retardancy, mechanical strength, and surface smoothness of the molded product. Here, the average particle size is the average particle size measured at 50% cumulative distribution particle size by a laser micron sizer method. As commercially available products of melamine cyanurate or melamine isocyanurate, MC-4000, MC-4500, MC-6000, etc. manufactured by Nissan Chemical Industries, Ltd. are preferably used.

[0031] The amount of the (B) component is 0.01 parts by weight or more and 30 parts by weight or less, based on 100 parts by weight of the (A) component, from the viewpoint of expandability. When the (B1) component is used, the lower limit of the amount of the (B) component is preferably 0.05 parts by weight or more, more preferably 0.1 parts by weight or more, from the viewpoint of expandability. When the (B2) component is used, on the other hand, 1 part by weight or more is preferable, and 5 parts by weight or more is more preferable. When the (B1) component is used, the upper limit of the amount of the (B) component is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, and particularly preferably 1 part by weight or less, from the viewpoint of moldability. When the (B2) component is used, on the other hand, 15 parts by weight or less is preferable, more preferably 13 parts by weight or less, and particularly preferably 10 parts by weight or less. In addition, it is preferable to use the (B1) component and the (B2) component in combination, since the foaming in a high-temperature environment can be stabilized and the foaming can be expanded more by using them in combination.

[0032] By further blending a heat stabilizer (C) (hereinafter sometimes referred to as component (C)), the thermoplastic resin composition can suppress decomposition of component (A) in a high-temperature environment and can increase the expandability.

[0033] The component (C) in the present invention is a compound containing a phenol group, a phosphorus atom, or a sulfur atom in order to capture the radicals generated during the thermal decomposition of the component (A) in a high-temperature environment, and specific examples thereof include hindered phenol compounds, phosphite compounds, hypophosphite compounds, and thioether compounds, and two or more of these can be blended. Phosphite compounds and hypophosphite compounds are preferred in terms of superior expansion properties, and among hypophosphite compounds, sodium hypophosphite is particularly preferred.

[0034] The amount of component (C) is preferably 0.01 to 1 part by weight based on 100 parts by weight of component (A). From the viewpoint of expandability, the lower limit of the amount of component (C) is more preferably 0.05 parts by weight or more, and particularly preferably 0.1 parts by weight or more. From the viewpoint of durability, the upper limit of the amount of component (C) is more preferably 0.5 parts by weight or less, and particularly preferably 0.3 parts by weight or less.

[0035] The thermoplastic resin composition of the present invention may contain any additives, such as a filler, an ultraviolet absorber, a light stabilizer, a plasticizer, a flame retardant, a release agent, a pigment, a dye, and an antistatic agent, within a range that does not impair the effects of the present invention.

[0036] The thermoplastic resin composition of the present invention can be obtained, for example, by melt-kneading the above-mentioned components (A) and (B), as well as the component (C) and, if necessary, other components.

[0037] Examples of the melt-kneading method include a method in which component (A), component (B), component (C), and various additives are premixed, and the premix is ​​fed to an extruder or the like and thoroughly melt-kneaded; or a method in which a predetermined amount of each component is fed to an extruder or the like using a quantitative feeder such as a gravimetric feeder, and thoroughly melt-kneaded.

[0038] Examples of the premixing include a dry blending method and a mixing method using a mechanical mixer such as a tumbler, ribbon mixer, or Henschel mixer. In addition, inorganic fillers such as fibrous reinforcing materials may be added by installing a side feeder between the entrance and vent of a multi-screw extruder such as a twin-screw extruder. In addition, in the case of liquid additives, a method of adding using a plunger pump by installing a liquid addition nozzle between the entrance and vent of a multi-screw extruder such as a twin-screw extruder, or a method of supplying from the entrance with a metering pump may be used.

[0039] The thermoplastic resin composition of the present invention is preferably pelletized before molding. Examples of the pelletizing method include a method in which the composition is extruded in the form of strands using a single-screw extruder, twin-screw extruder, triple-screw extruder, conical extruder, or kneader-type mixer equipped with a "Unimelt" or "Dulmage" type screw, and then cut with a strand cutter.

[0040] The molded article for protecting a battery of the present invention can be obtained by melt molding the thermoplastic resin composition. Examples of the melt molding method include injection molding, extrusion molding, and blow molding, with injection molding being particularly preferred.

[0041] As injection molding methods, in addition to the usual injection molding method, gas-assisted molding, two-color molding, sandwich molding, in-mold molding, insert molding, injection press molding, and the like are known, and any of these molding methods can be applied.

[0042] The molded body for protecting a battery of the present invention is a molded body designed to be placed in contact with a battery, and the thickness of the molded body is preferably 0.1 mm to 3 mm, and may be any shape such as a prismatic shape, a cylindrical shape, a cylindrical shape, etc. In the present invention, the thickness refers to the dimension of the molded body in the perpendicular component to the surface that contacts the battery.

[0043] The expansion coefficient in the thickness direction of the molded body for protecting a battery of the present invention in a high-temperature environment is preferably 1.3 or more, more preferably 1.5 or more, even more preferably 1.8 or more, and particularly preferably 2.0 or more, in terms of improving the safety of the battery. The upper limit of the expansion coefficient is 10. Note that a high-temperature environment is an environment of 200°C or more to 400°C or less, at which thermal runaway of the battery is caused, and by expanding in this temperature environment, the propagation of heat can be efficiently suppressed. The expansion coefficient in the present invention is determined from the ratio of thickness before and after heat treatment at a temperature of 380°C (thickness after heat treatment / thickness before heat treatment).

[0044] The method for adjusting the expansion coefficient of the battery protection molded body of the present invention to the above value is not limited as long as such a molded body can be obtained, but for example, it can be obtained by molding a thermoplastic resin composition in which 0.1 part by weight or more and 30 parts by weight or less of (B) are blended with 100 parts by weight of (A) component.

[0045] The battery protection molded article of the present invention is preferably used as a battery member for protecting batteries such as vehicle-mounted batteries, stationary cylindrical batteries, and pouch-type batteries. In particular, it is more preferably used as a battery member for vehicle-mounted batteries that require higher density and higher output. Specific examples of battery members include battery holding members, battery insulating caps, battery cases, battery terminal holders, and tab leads.

[0046] The molded article for protecting a battery of the present invention is placed around a battery, and the thickness of the molded article expands 1.3 to 10 times in a high-temperature environment of 200°C or higher and 400°C or lower, thereby suppressing heat propagation, and thus protecting the battery from thermal runaway. EXAMPLES

[0047] Next, the molded body for protecting a battery of the present invention will be specifically described with reference to examples. However, the present invention is not limited to the examples given here. Here, % and parts represent % by weight and parts by weight, respectively.

[0048] [Method of measuring each characteristic] In each of the examples and comparative examples, the characteristics were evaluated by the measurement methods described below.

[0049] 1. Expansion The resin composition of the sample was molded into a molded body having a width of 80 mm, a length of 80 mm, and a thickness of 1 mm using a NEX1000 injection molding machine manufactured by Nissei Plastics Co., Ltd., a mold consisting of a 0.8 mmt film gate and a cavity having a width of 80 mm, a length of 80 mm, and a thickness of 1 mmt under molding cycle conditions of a molding temperature of 280 ° C, a mold temperature of 80 ° C, an injection speed of 50 mm / s, a total injection time and pressure holding time of 10 seconds, and a cooling time of 10 seconds. A 50 μm thick aluminum sheet was laid on the lower press plate of a high-temperature heat press machine H400 manufactured by AS ONE Co., Ltd., set at 380 ° C as a high-temperature environment, and the molded body was placed on it and heat-treated for 5 minutes. After 5 minutes, it was taken out and cooled to room temperature, and the thickness was measured with a micrometer, and the ratio of the thickness before and after the heat treatment (thickness after heat treatment / thickness before heat treatment) was calculated as the expansion coefficient. An expansion ratio of 1.3 or more was judged to be excellent, 1.5 or more to be better, 1.8 or more to be even better, and 2.0 or more to be particularly excellent.

[0050] In addition, the surface temperature of the molded body during the heat treatment was measured using a thermograph (G100EX) manufactured by Nippon Avionics Co., Ltd., and the surface temperature 5 minutes after the heat treatment was evaluated as an index of heat propagation (heat propagation prevention property). A surface temperature of 280°C or less was judged to be excellent in heat propagation prevention property, 260°C or less was judged to be even better, and 240°C or less was judged to be particularly excellent.

[0051] 2.Compression creep properties The resin composition of the sample was molded under the same conditions as in item 1 above to obtain a molded body with a width of 80 mm, length of 80 mm, and thickness of 1 mm. The obtained molded body was placed in an environment adjusted to a temperature of 75°C in a thermostatic chamber TCR-1 manufactured by Shimadzu Corporation, and a cylindrical compression tool with a diameter of 10 mm was pressed against the molded body using a universal testing machine Autograph AG-50kNX manufactured by Shimadzu Corporation, and compressed to a compression stroke of 0.4 mm at a stroke speed of 1 mm / min to obtain an initial stress F1 (N). The state was further maintained, and the later stress F2 (N) after 20 minutes was obtained. The compressive stress retention rate was calculated as the percentage of the later stress F2 to the initial stress F1 (F2 / F1 x 100 (%)). A compressive stress retention rate of 50% or more was judged to be excellent in compressive creep resistance, 60% or more was judged to be even better, and 70% or more was judged to be particularly excellent.

[0052] 3. Molding stability The sample resin composition was molded under the same conditions as in item 1 above, and 50 shots were made to mold a molded body with a width of 80 mm, length of 80 mm, and thickness of 1 mm. The number of short shots, which are insufficient filling, was counted. The fewer the number of short shots, the better the molding stability was judged to be.

[0053] The raw materials used in the examples and comparative examples are as follows. Thermoplastic resin (A) (A-1) Polypropylene resin, melting point 160°C, J105G manufactured by Prime Polymer Co., Ltd., MFR 9.0g / 10min (measurement conditions: 230°C, 2.16kg load) (A-2) Polybutylene terephthalate resin: melting point 225°C, IV value 0.86, terminal carboxyl group amount 21eq / t (A-3) Polycarbonate resin, glass transition point 150° C., “LEXAN” 101, manufactured by GEPlastics, end-blocked with 4-α-cumylphenoxy groups was used. Thermoplastic resin (A') other than thermoplastic resin (A) (A'-1) Polyethylene resin (HDPE), melting point 130°C, manufactured by Prime Polymer Co., Ltd., 2200J, MFR 5.2g / min (measurement conditions: 230°C, 2.16kg load) Expansion agent (B): Melt tension imparting agent (B1) (B1-1) Polytetrafluoroethylene, manufactured by Mitsui DuPont Fluorochemicals Co., Ltd., "Teflon" (registered trademark) 6J (B1-2) Polymethyl methacrylate / butyl acrylate copolymer, Kaneka Corporation, "KANEACE" (registered trademark) PA-40 Expansion agent (B): Nitrogen-based foaming agent (B2) (B2-1) Melamine cyanurate, manufactured by Nissan Chemical Industries, Ltd., MC-4000 Compound (B') other than the expanding agent (B) (B'-1) Magnesium hydroxide, Fujifilm Wako Pure Chemical Industries, Ltd. Heat stabilizer (C) (C-1) Hindered phenol compound, pentaerythrityl-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]: Irganox (trademark) 1010 manufactured by BASF (C-2) Phosphite compound, bis(2,6-di-t-butyl-4-methylphenyl)pentaerythritol diphosphite: "ADEKA STAB" (registered trademark) PEP36 manufactured by ADEKA Corporation (C-3) Sodium hypophosphite, manufactured by Tokyo Chemical Industry Co., Ltd.

[0054] [Examples 1 to 13, Comparative Examples 1 to 6] Using a co-rotating, vented twin-screw extruder (TEX-30α, manufactured by Japan Steel Works) with a screw diameter of 30 mm and L / D of 35, components (A), (B), (C) and other additives were mixed in the composition shown in Table 1, and then added from the base charge section of the twin-screw extruder. Glass fibers were added using a side feeder installed midway between the base charge section and the vent section. Melt mixing was performed under extrusion conditions of a kneading temperature of 260°C and a screw rotation of 150 rpm, and the resulting resin composition was discharged in the form of strands, solidified through a cooling bath, and pelletized with a strand cutter.

[0055] The obtained pellets were dried in a hot air dryer at 110° C. for 6 hours and then evaluated by the above-mentioned method. The results are shown in Table 1.

[0056] [Table 1-1]

[0057] [Table 1-2]

[0058] A comparison of Examples 1 to 9 and Comparative Examples 1 to 5 reveals that a molded body made from a thermoplastic resin composition obtained by blending 0.01 to 30 parts by weight of an expansion agent (B) with 100 parts by weight of a thermoplastic resin (A) having a glass transition point or a melting point, whichever is higher, of 150°C or higher has excellent compression creep characteristics, an expansion coefficient of 1.3 or more, and excellent heat transfer prevention properties, and is therefore suitable as a molded body for protecting a battery.

[0059] Comparison of Example 10 with Examples 2 and 6 reveals that the combined use of the melt tension imparting agent (B1) and the nitrogen-based blowing agent (B2) provides superior expansibility and superior heat transfer prevention properties.

[0060] A comparison of Examples 11 to 13 with Example 10 revealed that the molded article made of a thermoplastic resin composition further containing a specific amount of a heat stabilizer (C) had better molding stability and expandability, and also had better heat propagation prevention properties.

[0061] Comparing Examples 2 and 6 with Comparative Example 6, it was found that when an endothermic material such as magnesium hydroxide is used, the molding stability decreases and the decomposition of the thermoplastic resin is accelerated, so that the expansion property decreases in a high temperature environment and the heat transfer prevention property cannot be obtained.

Claims

1. A molded body for protecting a battery, comprising a thermoplastic resin composition, the thermoplastic resin composition being prepared by blending 0.01 parts by weight or more and 30 parts by weight or less of an expansion agent (B) with 100 parts by weight of a thermoplastic resin (A) having a glass transition point or a melting point, whichever is higher, of 150°C or more and 300°C or less.

2. 2. The molded body for protecting a battery according to claim 1, which has a coefficient of expansion in a thickness direction when heat-treated in a high-temperature environment at 380° C. for 5 minutes of 1.3 or more.

3. 3. The molded body for protecting a battery according to claim 1, wherein the thermoplastic resin (A) is a polybutylene terephthalate resin, and the expanding agent (B) is a melt tension imparting agent (B1) consisting of a polymer containing a structural unit derived from at least one monomer selected from ethylene, fluoroethylene, styrene, and acrylic.

4. 3. The molded body for protecting a battery according to claim 1, wherein the thermoplastic resin (A) is a polybutylene terephthalate resin, and the expanding agent (B) is a nitrogen-based blowing agent (B2) selected from the group consisting of an aliphatic amine compound, an aromatic amine compound, a nitrogen-containing heterocyclic compound, a cyan compound, an aliphatic amide compound, an aromatic amide compound, urea, and thiourea.

5. 3. The molded article for protecting a battery according to claim 1, wherein the expansion agent (B) is polytetrafluoroethylene or a copolymer thereof.

6. 3. The molded article for protecting a battery according to claim 1, wherein the expanding agent (B) is polymethyl methacrylate or a copolymer thereof.

7. 3. The molded article for protecting a battery according to claim 1, wherein the expansion agent (B) is melamine cyanurate.

8. 3. The molded article for protecting a battery according to claim 1, wherein the thermoplastic resin composition further contains 0.01 to 1 part by weight of a heat stabilizer (C) per 100 parts by weight of the thermoplastic resin (A).

9. A method for protecting a battery, comprising: disposing the battery protective molded article according to claim 1 or 2 around a battery; and expanding the thickness of the molded article by 1.3 to 10 times in a high-temperature environment of 200° C. or higher and 400° C. or lower, thereby suppressing heat propagation.

Citation Information

Patent Citations

  • Current breaking mechanism of battery and battery pack provided with the current breaking mechanism

    JP2000197260A

  • Packaging material, laminate, and resin molded container

    JP2020158159A

  • Battery module

    WO2017125985A1